Management of Island Tourism Destinations in Sidoarjo Regency - Elisa Indah Suryani; Lailul Mursyidah (Universitas Muhammadiyah Sidoarjo, 2022)
Lusi Island is one of the tourist destinations in Sidoarjo which is expected to become an environmentally friendly tourist destination with the theme of utilization, research, and conservation of mangroves. Lusi Island is not widely known by the public because visitors are still dominated by the Jabon sub-district and the surrounding area. This study aims to analyze and describe the management and constraints in the Management of Tourism Destinations on Lusi Island in Sidoarjo Regency. The research method used is a qualitative approach, data collected through observation, interviews and documentation, while the data sources are primary and secondary data. Informants who were determined by interview, the informants were UPT BPSPL Wilker staff, East Java Directorate General of PRL, Lusi Island Guard and Head of the Sidoarjo Regency Tourism Office, data analysis derived from Miles and Huberman data, namely through data collection, data, data presentation and conclusions. The results of this study indicate that the process of managing Lusi Island has not been maximized because there are several inhibiting factors. As for some of these factors, there is no government intervention in the process of maintaining and developing the island and there is no legality on the island of Lusi in Sidoarjo Regency.